Motor vehicle crash fatalities at 30 days in Spain Fallecidos a 30 días por lesiones producidas en accidente de tráfico en España - Catherine Pérez; Eva Cirera; Carme Borrell; Antoni Plasència (Elsevier, 2006)
Objectives: To assess level of fulfilment and utility of the hospital discharge register (HDR) as a complementary source of information for estimating the number of deaths at 30 days due to motor vehicle crashes in Spain. Methods: It is a cros-sectional study were we compared the number of people injured due to motor vehicle crashes hospitalised in a public hospital (HDR), in Spain during 2001, with the number of people severely injured or killed due to motor vehicle crashes reported by the police database (Dirección General de Tráfico, DGT) for the same year. A descriptive analysis was carried out by age, sex and region (Autonomous Community), as well as an estimation of the percentage of under-reporting of deaths by the DGT based on two assumptions. Results: Police reported 27,272 severe injuries and 4,811 deaths during first 24 hours after the crash and after applying a fatality adjustment factor estimated 706 more deaths up to 30 days after the crash. The HDR reported 40,174 urgent hospitalisations. Of these, 1,099 died during the day of hospitalisation or within the following 30 days. The police only notified 68% of all cases that required hospitalisation. According to the number of deaths reported by police and contrasted with hospital register, estimations of the number of deaths at 30 days made by police could represent a level of under-reporting of between 3% and 6.6%, depending on the assumption considered. Conclusions: This study showed that the HDR is an information source that complements police statistics and is useful to estimate the number of deaths and non-fatal injuries due to motor vehicle crashes in Spain. Objetivos: Valorar el grado de cumplimiento y la utilidad del conjunto mínimo y básico de las altas hospitalarias (CMBDAH) para estimar el número de fallecidos a 30 días por accidente de tráfico (AT). Método: Las poblaciones del estudio fueron los heridos graves y fallecidos por AT registrados en la base de accidentes de la Dirección General de Tráfico (DGT) y los lesionados por AT ingresados en un hospital público. Se ha llevado a cabo un análisis descriptivo por edad, sexo y comunidad autónoma y una estimación del porcentaje de subnotificación de muertes de la DGT según dos asunciones. Resultados: Según la DGT, se registraron 27.272 heridos graves y 4.811 fallecidos en las primeras 24 h y se estimaron 706 fallecidos con la aplicación del factor de corrección a los 30 días. Según el CMBDAH, se produjeron 40.174 ingresos hospitalarios urgentes, en los que en 1.099 casos se produjo el fallecimiento el mismo día del ingreso o en los 30 días posteriores. Así pues, por la información obtenida por la policía, se detectó el 68% de los casos que requirieron ingreso hospitalario. Tomando como referencia el número de fallecidos según la DGT, completado por las muertes según el CMBDAH, las estimaciones de fallecidos a 30 días realizadas por la DGT fueron entre un 3 y un 6,6% inferiores según la asunción considerada. Conclusiones: Este estudio pone de manifiesto la utilidad de la información suministrada por el CMBDAH para la obtención de información sobre el número de fallecidos y heridos graves complementaria a las estadísticas policiales.